The Legal Efforts on Marine Culture Development in Pacitan, 1999-2015 - Heru Arif Pianto (Indonesian Historical Studies, 2017)
Beach is one of the most famous tourism areas in Pacitan. Beaches in Pacitan have special features compared to other beaches. The beautiful nature is able to attract tourists to come, visit and enjoy it. Therefore, the beaches in Pacitan have a lot of possibilities to be a tourism area of marine culture.This article is a historical research. The method used in this study was a historical research method, consisting of four steps, heuristics, criticism, interpretation and historiography. The results of this study indicate that the beaches in the Pacitan region have special attraction for tourists to visit.Thus, to be a tourism area of marine culture, Pacitan requires a better management. Based on research conducted so far, the beaches in Pacitan have not been managed optimally, due to a lack of facilities, and low human resources as managers. In short, it is the responsibility of communities, private parties and local governments to maximize the quality of management of coastal tourism around Pacitan, and their cooperation is need. Therefore, the beaches can be a tourist area of marine culture that can grow rapidly in Pacitan region.